Role of Polyfunctional Admixture Based on Silica Fume and Carbon Nanotubes in Forming the Structure of Gypsum Cement Composition. (2015) - Izryadnova, Olesya; Yakovlev, Grigory; Nurieva, Lilya; Sychugov, Stanislav; Pervuchin, Grigory
Abstract: One of the topical areas of regulating the structure of gypsum cement compositions is modifying the morphology with ultrafine and nanodisperse systems. The study has analyzed the possibility of changing the structure and properties of new formations of gypsum cement pozzolanic matrix by adding multifunctional admixture based on silica fume and multi-walled carbon nanotubes (MWCNTs) dispersed in a surfactant medium. The optimum content of complex admixture has been determined as 0.006% of MWCNTs and 10% volume content of silica fume as part of modified gypsum cement pozzolanic binder (GCPB) providing the increase of compressive strength by 55% and water resistance by 32%. Studying the structure of modified GCPB by means of physico-chemical analysis (scanning electron microscopy, infrared-spectral analysis and differential scanning calorimetry) has proved the improvement of physical and mechanical properties due to changes in mineralogical composition of new formations in hardening composition and morphology of the forming crystal hydrates in the structure of modified gypsum cement pozzolanic matrix. At the same time, it is noted that gypsum crystalline hydrates are coated with calcium silicate hydrates compacting the structure of the composition and increasing the total contact surface of the new formations. At the same time calcium silicate hydrates prevent water from the surface of crystals of calcium sulfate dihydrate, thereby increasing the water resistance of the composition.